The Effect of Half Squat Jump and Hurdle Jump Training on Short Distance Running of 60 Meters in Class IX Students of SMP Negeri 11 Makassar - Ahmad Dani; Sudiadharma Sudiadharma; Hikmad Hakim; Arimbi Arimbi; Muh. Adnan Hudain (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to test the effect of half squat jump and hard jump training on short-distance running of 60 meters. The method used in this research is experimental research. This research was conducted at SMP Negeri 11 Makassar with participants in this research being students who were willing to follow all research procedures. The sample in this research was 20 students. The instrument used in this research was a 60-meter short-distance running test. Based on the results of data analysis, it can be concluded that the half squat jump training and hurdle jump training on the ability to run a short distance of 60 meters in class IX students of SMP Negeri 11 Makassar, obtained the average value of the half squat jump training group, namely 9.716, which is smaller than the average value of the half squat jump training group. The average for the hurdle jump training group was 9.082 with a value of t-count = 2.244 > t-table = 2.101 or significant 0.038 < 0.05. The results of this study show that hardle jump training is better than half squat jump training for short-distance running of 60 meters in class IX students of SMP Negeri 11 Makassar.